1990
DOI: 10.1037/0735-7028.21.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Drawing on clinical practice to inform research on child and adolescent psychotherapy: Survey of practitioners.

Abstract: This study was designed to draw on clinical practice as a way of identifying priority areas for child and adolescent psychotherapy research. 1,162 psychologists and psychiatrists described several features of their clinical work and evaluated the effects of alternative treatment approaches, factors that influence therapeutic change, and the priority of alternative types of research. The majority agreed on (a) the importance of several specific child, parent, and therapist factors that contribute to outcome, (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
199
0
4

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(208 citation statements)
references
References 27 publications
4
199
0
4
Order By: Relevance
“…To accomplish this, we selected a random sample of 150 child and adolescent therapists from the National Register of Health Service Providers in Psychology (Council for the National Register of Health Service Providers in Psychology, 1989Psychology, , 1990), and we tabulated therapists' listed theoretical orientations. Very specific orientations were counted as examples of broader approaches (e.g., social learning as "behavioral," psychoanalytic as "psychodynamic"), reflecting both our understanding of their shared theoretical underpinnings and the classification of orientations used in the Kazdin, Siegel, et al (1990) survey of practicing therapists. As we expected, many of our sampled therapists listed multiple orientations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this, we selected a random sample of 150 child and adolescent therapists from the National Register of Health Service Providers in Psychology (Council for the National Register of Health Service Providers in Psychology, 1989Psychology, , 1990), and we tabulated therapists' listed theoretical orientations. Very specific orientations were counted as examples of broader approaches (e.g., social learning as "behavioral," psychoanalytic as "psychodynamic"), reflecting both our understanding of their shared theoretical underpinnings and the classification of orientations used in the Kazdin, Siegel, et al (1990) survey of practicing therapists. As we expected, many of our sampled therapists listed multiple orientations.…”
Section: Methodsmentioning
confidence: 99%
“…First, the psychotherapy provided in most studies may differ in important ways from the care provided routinely by real-world clinicians. For example, it has been reported that typical clinical practice tends to be less structured, less behavioral, and more eclectic than most manualized research therapies (see, e.g., Kazdin, Siegel, & Bass, 1990;Weisz, Weiss, & Donenberg, 1992). Second, the few studies that have examined child psychotherapy in realworld clinical settings generally have not specified either their models of intervention or the specific therapy procedures used.…”
mentioning
confidence: 99%
“…In contrast to the extensive empirical work examining the alliance-outcome link in therapy with adults, there has been a relative paucity of such research in treatment with children and adolescents (Kazdin, Siegel, & Bass, 1990;Shirk & Saiz, 1992). A recent meta-analysis, covering the years 1973-2000, included only 18 published studies and five unpublished doctoral dissertations that investigated the association between the therapeutic relationship and outcome among children and adolescents (Shirk & Karver, 2003).…”
mentioning
confidence: 99%
“…Individual variation between therapists is minimized by extensive training in the manualized techniques, and treatment adherence is monitored. The conduct of therapy in the real world bears little resemblance to this model, and the services provided to depressed youth in community settings are likely quite eclectic and dependent on individual therapists' preferences and skills (Addis & Krasnow, 2000;Kazdin, Siegel, & Bass, 1990;Weersing, Weisz, & Donenberg, in press). Recent broad-based services research has suggested that the effects of this eclectic community treatment may be much more modest than the effects of therapy in RCTs (see, e.g., Bickman, 1996;Weiss, Catron, Harris, & Phung, 1999).…”
mentioning
confidence: 99%